Implanting Atomic Cobalt within Mesoporous Carbon toward Highly Stable Lithium–Sulfur Batteries - Xie, Jin; Li, Bo‐Quan; Peng, Hong‐Jie; Song, Yun‐Wei; Zhao, Meng; Chen, Xiao; Zhang, Qiang; Huang, Jia‐Qi (Advanced materials (Weinheim), 2019)
Lithium–sulfur (Li–S) batteries hold great promise to serve as next‐generation energy storage devices. However, the practical performances of Li–S batteries are severely limited by the sulfur cathode regarding its low conductivity, huge volume change, and the polysulfide shuttle effect. The first two issues have been well addressed by introducing mesoporous carbon hosts to the sulfur cathode. Unfortunately, the nonpolar nature of carbon materials renders poor affinity to polar polysulfides, leaving the shuttling issue unaddressed. In this contribution, atomic cobalt is implanted within the skeleton of mesoporous carbon via a supramolecular self‐templating strategy, which simultaneously improves the interaction with polysulfides and maintains the mesoporous structure. Moreover, the atomic cobalt dopants serve as active sites to improve the kinetics of the sulfur redox reactions. With the atomic‐cobalt‐decorated mesoporous carbon host, a high capacity of 1130 mAh gS−1 at 0.5 C and a high stability with a retention of 74.1% after 300 cycles are realized. Implanting atomic metal in mesoporous carbon demonstrates a feasible strategy to endow nanomaterials with targeted functions for Li–S batteries and broad applications. Atomic cobalt implantation to mesoporous carbon enhances the sulfur kinetics in Li–S batteries. Atomic cobalt dopants with high polarity endow the mesoporous carbon (represented by the apes) with high affinity with polysulfides (represented by the bananas). Therefore, the shuttle effect is eliminated and the sulfur kinetics is improved, facilitating highly stable Li–S batteries.